The social trust and leadership roles : revitalising duty bearer accountability in the protection of social and economic rights in Malawi and Uganda - Twinomugisha, Ben (University of Pretoria, 2006)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2005.